The mimetic politics of lone-wolf terrorism - Brighi, Elisabetta (Journal of international political theory, 2015)
Written at a time of crisis in the project of social and political modernity, Fyodor Dostoevsky?s 1864 novel Notes from Underground offers an intriguing parallel for the twenty-first century lone-wolf; it portrays an abject, outcast, spiteful unnamed anti-hero boiling with rage, bitter with resentment and on the verge of radicalisation. A Girardian reading of the poetic truths contained in Dostoevsky?s work is able to provide important keys to explain the contemporary transformation from ?fourth-wave? religious terrorism to ?fifth-wave? lone-wolf terrorism. Such a reading argues that it is mimetic rivalry ? rather than much-trumpeted forms of religious violence or cultural differences ? that fuels the triangular relation between governments, terrorists and civilian victims at heart of terrorist acts. This approach is further able to blend social inquiry with an account of the individual, in fact anthropological, conditions of lone-wolf terrorism by tracing the globalisation of resentment and the individualisation of violence to the hyper-mimeticism characterising the globalisation of late modernity. Finally, a mimetic reading of ?fifth-wave? terrorism accounts for the turbulence of a global politics in which victimhood and scapegoating no longer have the ability to stabilise social order and warns against a future where violence proliferates and escalates unchecked.